Experimental and simulation studies on the mechanical performance of concrete T-Girder bridge strengthened with K-Brace composite trusses. (September 2022) - Hou, Peng; Yang, Jing; Pan, Yong; Ma, Changjun; Du, Wenping; Yang, Caiqian; Zhang, Yang
Abstract: In this paper, a new transverse strengthening method was proposed for T-girder bridges with K-brace composite trusses. A series of experiments and simulations were conducted to study the strengthening effects under four different loading conditions, including non-eccentric loading, transverse eccentric loading, longitudinal eccentric loading, and bidirectional eccentric loading modes. Altogether four groups of specimens were fabricated and studied. Each group consisted of a control specimen and a strengthened one. Furthermore, the concrete plastic damage model was used to simulate the mechanical behaviors of the specimens. The results showed that such a strengthening method could significantly upgrade the mechanical behaviors of the T-girder bridge specimens, especially the local deformation and crack propagation manner of the T-girder. Compared with the control specimen, the deflection of concrete T-girder bridge specimen strengthened with the K-brace composite trusses was significantly decreased, with a maximum reduction of 38.6% under the prescribed load. Moreover, the K-brace composite trusses can markedly better the load distribution and improve the failure modes of the specimens, where the crack widths decreased even by 44.0%. They distributed along the beam more evenly. So, it provides a new method to strengthen and upgrade the mechanical properties of T-girder bridges.